2023
DOI: 10.1007/s12649-023-02101-y
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Antibacterial Ag/Graphene-Integrated Non-woven Polypropylene Textile for Air Pollutant Filtering

Abstract: Air pollution and infectious diseases (such as the COVID-19 pandemic) have attracted considerable attention from governments and scientists worldwide to find the best solutions to address these issues. In this study, a new simultaneous antibacterial and particulate matter (PM) filtering Ag/graphene-integrated non-woven polypropylene textile was fabricated by simply immersing the textile into a Ag/graphene-containing solution. The Ag/graphene nanocomposite was prepared by reducing Ag ions on the surface of grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Despite this appearing interesting for actual application, its cost may be too high. La et al [ 53 ] recently reported an Ag/graphene-integrated nonwoven polypropylene filter, which is prepared by reducing Ag ions on the surface of graphene nanoplatelets (GNPs) using plant extract. Shiu et al [ 54 ] developed a new filter prepared by Ag@ZIF-8@PP melt-blown nonwoven fabrics with higher air filtration and antibacterial efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this appearing interesting for actual application, its cost may be too high. La et al [ 53 ] recently reported an Ag/graphene-integrated nonwoven polypropylene filter, which is prepared by reducing Ag ions on the surface of graphene nanoplatelets (GNPs) using plant extract. Shiu et al [ 54 ] developed a new filter prepared by Ag@ZIF-8@PP melt-blown nonwoven fabrics with higher air filtration and antibacterial efficacy.…”
Section: Introductionmentioning
confidence: 99%